PERAN DOSEN TERHADAP PEMBINAAN MAHASISWA BERBASIS KOMPETENSI - Tasbih, Tasbih (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2021)
The main problem in this literature review is how is the role of lecturers in developing competency-based students is translated into two sub-problems, namely what is the professional attitude needed by a lecturer in student development? and how do lecturers respond to the professional demands of competency-based student development? The results of the analysis show that the professional attitude of the lecturers is a necessity in the context of efficiency and effectiveness in serving so that the potential of students develops according to their talents and abilities. This attitude of professionalism requires academic skills, mental, social, and spiritual skills. Meanwhile, the way lecturers respond to the demands of professionalism is by doing careful preparation and planning as well as directed work, so that evaluations can be carried out both at the class level and at the institutional level. The implication is that the synergy of all stakeholders is needed to support competency-based student development.